The exigencies of student participation in university governance: Lip services and bottlenecks. (21st October 2019) - Tamrat, Wondwosen
Abstract: This study was conducted to explore the level, type and quality of student participation in the governance milieu of twenty public universities in Ethiopia based on secondary data availed at a national level. The findings reveal that despite their demands and aspirations, students' participation in university governance is still at its lowest ebb across most of Ethiopian public universities both in terms of their representation at the available hierarchical structures and the quality of participation in matters of substantial importance to the student body. Given the multitude of advantages the institutions and students can garner from meaningful student participation, it is argued that changes need to be made in terms of improved representation, type and quality of student participation. Abstrait: Cette étude a été conduite pour explorer le niveau, la variété et la qualité de la participation étudiante dans le milieu gouvernance des 20 universités publiques en Ethiopie, basés sur des données secondaires utilisés au niveau national. Les données indiquent que malgrè leurs demandes et ambitions, la participation des étudiants dans la gouvernance universitaire reste toujours â son plus bas reflux â travers presque toutes les universités publiques éthiopiennes que ce soit en leur représentation de la structure hiérarchiquement disponible et la qualité de participation en ce qui concerne l' importance substancielle du corps étudiant. Les institutions et les étudiants, suivant les multiples avantages, peuvent receuillir autant de la participation étudiante. Il a ete donc discute que des changements importantes doivent etre portes soit dans la représentation que dans la qualité et la diversité de la participation étudiante.